Urban-Rural Variation of Early Marriage among Married Women in Babile Town and Its Environs, Oromiya National Regional State, Ethiopia - Abdumalik, Mohammed; Sishaw, Tegegne; Akmel, Awol (Ethiopian Journal of Social Sciences, 2018)
All over the world, within a single day a large number of girls are getting into marriage as early as their childhood without their will and consent.Â Likewise, in Ethiopia, women tend to marry considerably earlier than men. The objective of this study is to explore the rural-urban variation of early marriage among married women and the causative factors of variation. A crosssectionalÂ research design was adopted, and a total of 385 household heads (HHHs) were randomly selected as samples for this study, i.e. 206 from the urban and 179 from rural kebele. Chi square and binary logistic regression were used to analyze the data. The results of the study revealed that the prevalence of early marriage in Babile town and its environs was 48.8%. The variation among rural and urban women was 61.5% for rural vs. 37.9% for urban. Furthermore, early marriage both in rural and urban areas of the study area was caused by different socioeconomicÂ and cultural factors. Accordingly, current age, educational status, parental control, cultural as well as religious influences and ethnicity were the main factors significantly associated with early marriage. Findings from this study demonstrate the magnitude of the problem and the urgent need for the involvement of all actors to address the challenge.